Maximizing energy efficiency in partial loads of a multigroup hydroelectric power station integrated within the national interconnected system - Gonzales Chávez, Salome (2015)
In multigroup hydroelectric plant operating at partial loads, the maximum each group efficiency and the random combination of these, differ from the design efficiency of the plant at full load. These plants are conditioned to operate at partial loads, both in times of drought and periods of oversupply national electric grid. The period of drought in Peru is nine months per year, a situation that involves economic losses due to inadequate flow regulation and group choice efficiencies conditions below their optimum values. The aim of this work is the development optimizing efficiency process of a multigroup hydroelectric power plant, for any level of power generated in the daily interconnected generation program. The results are maximizing turbine efficiency and combined-group for each power output of the plant, outside its nominal conditions, also a computer program is constructed in Matlab to integrate the automated system of hydroelectric power plant. Its application can reduce generation costs and increases plant availability; also forms a methodological pattern of use in other multigroup hydroelectric plants .